2005
DOI: 10.1370/afm.258
|View full text |Cite
|
Sign up to set email alerts
|

Women's Perceptions of Future Risk After Low-Energy Fractures at Midlife

Abstract: PURPOSE Low-energy fractures experienced by women at midlife and beyond place them at increased risk of future fractures and may be early indicators of low bone density. We report here on women's postfracture narratives to provide insight into how family physicians might tailor their messages to patients in communicating risk.METHODS An interview guide was used in face-to-face interviews with women aged 40 years and older. Patients were asked to describe their fracture experience and recovery during the subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…1 A strong predictor of patients' readiness for medical treatment and preventive behavior is their perceived vulnerability to disease. [2][3][4][5][6] The family history forms a basis upon which a person assesses his or her own vulnerability to common chronic diseases, 7,8 and the family history is becoming increasingly important as a medical devise to predict risk of future disease.…”
mentioning
confidence: 99%
“…1 A strong predictor of patients' readiness for medical treatment and preventive behavior is their perceived vulnerability to disease. [2][3][4][5][6] The family history forms a basis upon which a person assesses his or her own vulnerability to common chronic diseases, 7,8 and the family history is becoming increasingly important as a medical devise to predict risk of future disease.…”
mentioning
confidence: 99%
“…Aiming a post-fracture intervention at such patients fits the Teachable Moment framework because this framework emphasizes the importance of using a strong emotional response to a cueing event in building a 'teachable moment' and motivating subsequent behaviour change. Teachable Moment was previously mentioned in the context of post-fracture care by two authors [12,81]: One suggested that fractures were excellent teachable moments to educate patients about the importance of osteoporosis care while the other concluded that many patients have misperceptions about their osteoporosis and fracture risks and that physicians can use fractures as teachable moments to deliver health information and, more importantly, make this information relevant for patients.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical frameworks previously suggested in the context of osteoporosis management [12,81] should be tested. More research identifying intervention gaps from the patient's perspective should also be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The authors identify 3 belief systems among women in this study, which seem to call for different clinical approaches to individualizing care.…”
mentioning
confidence: 96%